Daun Pepaya (Carica Papaya) dan Serai (Cymbopogon citratus) Sebagai Pestisida Nabati Belalang Kayu (Valanga nigricornis) - Rifkah Akmalina; Maya Lukita; Khusnul Khotimah; Herlin Handini; Rismawati Rismawati (Jurnal Ilmiah Teknik Kimia, 2023)
The use of chemical pesticides to control grasshopper attacks harms the environment and people. Therefore, botanical pesticide as an alternative to a safer environment is needed. This study aims to determine the effectiveness of papaya leaves (Carica papaya) and lemongrass (Cymbopogon citratus) combination extracts against Javanese grasshopper based on maceration time and concentration variations, and to determine its compounds. The maceration time was 3, 5, and 7 days, and 30, 50, and 70% concentrations were used. The study showed that a 7 days maceration with 70% extract concentrations is the most effective to kill the Javanese grasshopper with an average mortality rate of 100%. Botanical pesticides are known to contain tannins, flavonoids, terpenoids, steroids, and citronellal. The presence of these compounds in the botanical pesticides causes Javanese grasshoppers which eat plants that have been sprayed to experience death due to poisoning and continuous loss of fluid.